The nice case of the greek inspector - Cristóbal Barea Romero (ADIDE Federación, 2016)
It is described the disappearance of the Inspector of Education in the Greek educational system and the recent discussion on recovery or not on the context of political and social changes of modern Greece. This portrait is described within the political and social historical area of Greece. Finally, conclusions about the institution of inspector of education and its relevance in the European context are extracted. No direct similarities are established with the Spanish case.